1995
DOI: 10.1111/j.1399-6576.1995.tb04148.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylmethacrylate monomer produces direct relaxation of vascular smooth muscle in vitro

Abstract: Methylmethacrylate bone cement is associated with severe hypotensive reactions during surgery and anesthesia. The purpose of this in vitro study was to determine if methylmethacrylate monomer could produce hypotension by acting directly on vascular smooth muscle. Segments of human saphenous vein or rabbit thoracic aorta were cut into rings. The rings were mounted in isolated tissue chambers in order to measure isometric tension development. Methylmethacrylate monomer (methylmethacrylic acid ester) produced dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 23 publications
1
21
1
3
Order By: Relevance
“…It has been reported that methyl methacrylate (MMA) may be teratogenic and can cause adverse cardiovascular effects in animals (Phillips et al, 1971, Singh et al, 1972Karlsson et al, 1995). In addition, subcutaneous polymethyl-methacrlylate implants induced malignant tumors in rodents (Oppenheimer et al, 1955).…”
Section: (G) Pulp Studies In Animals and Humansmentioning
confidence: 99%
“…It has been reported that methyl methacrylate (MMA) may be teratogenic and can cause adverse cardiovascular effects in animals (Phillips et al, 1971, Singh et al, 1972Karlsson et al, 1995). In addition, subcutaneous polymethyl-methacrlylate implants induced malignant tumors in rodents (Oppenheimer et al, 1955).…”
Section: (G) Pulp Studies In Animals and Humansmentioning
confidence: 99%
“…[1][2][3] The aetiology of these cardiovascular changes is unknown. Fat and marrow embolism, 4-6 the peripheral vasodilatation effect of the cement monomer, 7,8 and activation of the clotting cascade in the lungs 9 may all play a role.…”
mentioning
confidence: 99%
“…Previously Karlsson et al (17) demonstrated that MMA monomer produces direct relaxation via calcium mobilization in human saphenous vein and rabbit thoracic aorta. Similarly, the calcium antagonistic effect of MMA has been demonstrated in isolated rat uterus (18).…”
Section: Discussionmentioning
confidence: 98%